Protecting Emergency Responders with Evidence-Based Interventions (PEREI): protocol for a randomized controlled trial for early career emergency responders, significant others, and supervisors - Reginald D.V. Nixon; Marja Elizabeth; Daniel B. Fassnacht; Joep van Agteren; Laura C. Edney; Jennifer Wild (European Journal of Psychotraumatology)
Background: Emergency service personnel perform roles associated with high levels of trauma exposure and stress, and not surprisingly experience greater risk for poor mental health including posttraumatic stress disorder (PTSD), depression, anxiety, and substance use relative to the general population. Although programs exist to minimise the risk of developing mental health problems, their efficacy to date has been limited or untested. We will test the efficacy of the three programs which form PEREI: Protecting Emergency Responders with Evidence-Based Interventions. PEREI consists of modified versions of internet-delivered cognitive training in resilience (iCT-R) for early career first responders, PEREI-S for supervisors, and Be Well for Significant Others (BW-SO).Method: Up to 450 members in their first 5 years of service across multiple agencies will be recruited, with their adult supports (significant others, friends) invited to participate. Up to 180 supervisors in the agencies will be recruited. Participants will be randomized to their respective program or to receive the standard practice for mental health offered by the service (or usual mental health support for significant others). Assessments will be conducted pre- and post-program, and at 6- and 12-month follow-up. Primary outcome is PTSD and depression severity and probable-diagnosis. Secondary measures will index hypothesized mediators and moderators of outcome and determine whether the programs are cost-effective.Conclusions: The results will provide evidence as to efficacious methods for reducing risk of mental health problems in high-risk occupations, a better understanding of how such interventions may work, and whether they are good value for money.Trial registration: www.anzctr.org.au (ACTRN12622001267741)